Participation of Forest Users' Committee Members in Community Forestry Activities in the Midhills of Nepal - Gajurel, Kishor Prasad (1990)
The objectives of this study were to determine: (i) forest Users' Committee (FUC) formation process; (ii) the level of participation of Forest Users' Committee members; and (iii) association of personal, cognitive, attitudinal and situational factors with the level of participation. Altogether 105 respondents were selected using a simple random sampling technique from 16 committees in Lamjung and Dolakha Districts. Data were collected by means of personal interviews. Data were analysed using computer sub-programmes of the Statistical Package for Social Science (SPSS PC+). The findings revealed: members were among the elites in the Nepalese rural social system; (ii) some committees were formed under the initiation of villagers while some were induced by the forest off ice; (iii) the overall level of participation was low; 40 percent of the respondents were non-participants; 22 percent, 21 percent and 17 percent of them were low, medium and high participants respectively. (iv) The following factors were found to be significantly related with the level of participation: level of education (r=.42), trainings attended (C=.28), source of income (C=.33), perception of the roles and functions of Forest Users' Committees (r=.62), awareness about roles and functions of the change agency (r=.58), perception of problems (r=.48), attitude towards Forest Users' Committee (r=.76), sociability (r=.66), cosmopoliteness (r=.53), extens ion contact (r=.42) and political affiliation (r=.47). Among eighteen variables, only six variables were the important predictors of the FUC members' level of participation. The most important predictor was the attitude towards FUC . The other predictors of the FUC members' level of participation were: Sociability, Awareness about the roles and functions of change agency, perception of the problems, political affiliation, and perception of the roles and functions of FUC. The study recommended that the indigenous committees (if in existence) should be strengthened. Further, the formal committees should only be formed with the full consultation of the users. The Forest Users' Committees should be given legal status and that the procedure for its formation, its duties, functions and legal authority should be well defined. Also, the extension programme should be aimed at helping users to help themselves, facilitating a two-way flow of information between foresters and users, and working with the users rather than for the users.